STUDI LITERATUR PERKEMBANGAN KEMAMPUAN BAHASA ANAK USIA 4-6 TAHUN BERCERITA - Shofia, Siti; Dirgayunita, Aries (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
The primary objective of this research is to delineate the language capabilities of children using storytelling techniques. The investigation is prompted by the widespread difficulty children face in achieving proficient language skills. Inadequate language teaching methods for children have resulted in diminished interest in their linguistic progress. To address this issue, effective learning models tailored to individual needs need to be implemented. This study employs a literature review approach, scrutinizing various sources such as books, articles, and journals. The results emphasize the effectiveness of storytelling in augmenting language development in children. Storytelling is not only effective in fostering enjoyment during listening sessions but also in facilitating children to narrate their own stories. This conclusion is corroborated by a comprehensive analysis of relevant research findings, highlighting storytelling as a crucial strategy for improving language skills in early childhood. Keywords: Language Storytelling, Early Childhood